Gendered Perceptions in Maize Supply Chains: Evidence from Uganda - Van Campenhout, Bjorn; De, Anusha (Wiley, 2023)
Faced by imperfect information about the performance of value chain actors, transactions are often based on perceptions. Inaccurate perceptions may result in inefficient value chains. Biased perceptions, especially about women, may affect inclusiveness. We aim to compare perceptions by farmers, input dealers, traders and processors in Uganda’s maize value chain. Specifically, we compare ratings given by farmers to self-ratings of dealers, traders and processors. We test if male farmers rate others differently than female farmers do; if men and women rate themselves differently; and whether female farmers rate female value chain actors higher being of the same gender (homophily). A random sample of 1,526 small-scale farmers growing maize from Eastern Uganda were asked to rate agro-input dealers, traders and processors by ease of access, quality of services, price competitiveness, and reputation. These value chain actors — 78 agro-input dealers, 341 assembly traders and 174 processors — were then asked to assess themselves. Descriptive analysis, t-tests and multivariate regression with two-way non-nested clustering were used for the analysis. We find that input dealers, traders and processors rate themselves higher than farmers rate them. For self-assessments, the gender of the value chain actor does not matter. Female farmers tend to rate the dealers, traders and processors more highly than male farmers do. The sex of the actor rated does not affect the rating they receive: we also find no signs that women rate women more highly than they rate men. It is reassuring to see that in Eastern Uganda, women as dealers, traders and processors were not rated lower than their male counterparts. It was equally reassuring to see that dealers, traders and processors were rated well for quality by farmers — a frequent concern in Uganda is that they provide poor services. They did not score so well, however, for competitive prices. Policies to encourage competition and new entrants may help. That dealers, traders and processors rate themselves more highly than farmers do, could lead to complacency, hindering investment and innovation. The gap in perceptions might be reduced if there were certification by an independent agency, or if farmer ratings were crowd-sourced.